Analisis Sebaran Konsentrasi Karbon Monoksida (CO) Udara Ambien Dari Volume Kendaraan Dengan Menggunakan Model Gaussian Line Source (Studi Kasus Jalan Kenjeran, Jalan Oso Wilangun, dan Jalan Taman Sidoarjo) - Rachmad Dwi Prasetyo; Anak Agung Gde Kartika; Arie Dipareza Syafei (Racic : Rab Construction Research, 2025)
Air pollution often occurs in large cities and industrially dense areas that produce a lot of gases containing substances above normal limits such as carbon monoxide, nitrogen dioxide, sulfur dioxide, particulates, and so on. One of the main causes of air pollution is transportation and high traffic volumes that cause a decrease in ambient air quality. Motor vehicles contribute about 64% of carbon monoxide (CO) and to find out the distribution of these emissions, calculations with the Tier 2 Method and line model dispersion are needed because they have high accuracy between the model and existing conditions. The study was conducted on arterial roads with wide road conditions and crowded vehicles such as Kenjeran Road, Oso Wilangun Road, and Taman Sidoarjo Road. From the three roads, the highest CO concentration was obtained at a distance of 1 meter from the emission source but with different times. Kenjeran Street with the highest concentration was recorded at 17.00-18.00 WIB at 3.049 gr/m³ on, Oso Wilangun Street the highest concentration occurred at 08.00-09.00 WIB at 1.126 gr/m³, while on Taman Sidoarjo Street the highest concentration was recorded at 13.00-14.00 WIB at 1.75 gr/m³.